(untitled) (Veterinária Notícias, 2022)
Otitis externa are one of the most frequent diseases in the clinical routine of dogs and cats and they can cause by several associated factors. Due to incorrect use of antimicrobial, the treatment and the control of otitis have become challenging. The objective of this study is analyze results of otological examinations of the Laboratory of Microbiology in 2020, and to demonstrate the profile of patients and isolated bacteria. Staphylococcus was the main genus isolated and 71,11% of samples showed multi drug resistance to antimicrobial tested. This results show the need to use of complementary exams to control of otitis externa. Keywords: canines, felines, otological diseases, antimicrobial susceptibilities.